Overexpression of Chickpea Defensin Gene Confers Tolerance to Water-Deficit Stress in Arabidopsis thaliana - Kumar, Manoj; Yusuf, Mohd Aslam; Yadav, Pooja; Narayan, Shiv; Kumar, Manoj (Frontiers in Plant Science, 2019)
Plant defensins are mainly known for their antifungal activity. However, limited information is available regarding its function in abiotic stresses. In this study, a defensin gene, Ca-AFP, from Cicer arietinum, commonly known as chickpea, was cloned and transformed in Arabidopsis thaliana for its functional characterization under simulated drought stress conditions. Under simulated drought conditions (mannitol and polyethylene glycol-6000 induced), the transgenic A. thaliana plants had higher accumulation of the Ca-AFP transcript compared to that under non-stress condition and showed higher germination rate, root length, and biomass than the wild-type (WT) plants. To get further insights into the role of Ca-AFP in drought tolerance, we determined various physiological parameters and found significant reduction in the transpiration rate and stomatal conductance whereas the net photosynthesis and water use efficiency was increased in the transgenic plants compared to that in the WT plants under water deficit conditions. The transgenic plants showed enhanced superoxide dismutase, ascorbate peroxidase, and catalase activities, had higher proline, chlorophyll, and relative water content and exhibited reduced ion leakage and malondialdehyde content under drought conditions. Overall, our results indicate that overexpression of Ca-AFP could be an efficient approach for conferring drought tolerance in plants.